Pragmatisme Politik Luar Negeri Amerika dalam Pemberlakuan Lend-Lease Act 1941 - Azmi, Alia - (TINGKAP, 2013)
This article explains the role of the philosophy of pragmatism in American foreign policy and its development during the eve of World War II when Germany began to expand his power in Europe. Pragmatism is one of the philosophies that influence American thinking, which is embedded in its society. By elaborating the attitudes that are based on pragmatism and the political history of American foreign policy, the author explains American foreign policy to maintain its national interests even if it was contrary to its foreign policy means. The policy can be seen in the enactment of Lend-Lease Act which allows the U.S. President to provide military assistance to countries involved in the European war at the end of 1930s and the beginning of 1940s, despite the U.S. being in a neutral position on the war in Europe. Kata Kunci: pragmatisme, pragmatisme politik, politik luar negeri